The Human Auditory System Basic Features and Updates on Audiological Diagnosis and Therapy - Hatzopoulos, Stavros; Ciorba, Andrea; Skarzynski, Piotr H. (IntechOpen, 2020)
This book presents the latest findings in clinical audiology with a strong emphasis on new emerging technologies that facilitate and optimize a better assessment of the patient. The book has been edited with a strong educational perspective (all chapters include an introduction to their corresponding topic and a glossary of terms). The book contains material suitable for graduate students in audiology, ENT, hearing science and neuroscience.